DIFFERENCES IN MOTOR ABILITIES OF BOYS PARTICIPANTS OF THE ATHLETIC SESSIONS - Miloš Petrović (Sport Scientific And Practical Aspects, 2025)
In a sample of 164 participants of athletic sessions, aged 12-14 years who were divided into three subsamples per year, were implemented 8 tests. The problem of research was to analyze the manifestation of motor abilities of boys involved in the athletic section and to imply the existence of quantitative and qualitative differences in the manifestation of motor skills. The goal was to determine differences in motor abilities of boys involved in the athletic sections. Multivariate analysis of variance has shown the existence of statistically significant differences between age groups of boys. Discriminative analysis has shown two statistically significant discriminate factors that indicate the existence of considerable qualitative differences in motor abilities between boys of 12-14 years of age. After examining the maximum value of anthropometric and motor variables accelerants in the growth and development could be identified. These results could also be used in physical education for the evaluation of the effects of training program in athletic sections and making assessment of the results of development and physical quality.